2011
DOI: 10.1007/s00436-011-2341-4
|View full text |Cite
|
Sign up to set email alerts
|

Fasciola hepatica: time-dependent disruption of spermatogenesis following in vivo treatment with triclabendazole

Abstract: Sheep infected with the Cullompton isolate of Fasciola hepatica were treated with triclabendazole at a concentration of 10 mg/kg at 12 weeks post-infection. Adult flukes were recovered from the liver and, where present, from the gall bladder at 48, 72 and 96 h post-treatment (pt). Gross changes to the spermatogenic cells of the testis were examined by histology and ultrastructural alterations were visualised via transmission electron microscopy. Disruption was progressive in nature, with the testis tubules bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 20 publications
4
13
0
Order By: Relevance
“…The morphological characteristics observed for the control animal are consistent with those observed by Hanna et al (2008Hanna et al ( , 2010, McConville et al (2010), and Toner et al (2011) for F. hepatica specimens not exposed to anthelmintic. Spermatogonia and primary spermatocytes were observed to occupy the entire region of the testis tubule, thereby ensuring the production of viable sperm and, consequently, F. hepatica eggs.…”
Section: Microscopic Alterationssupporting
confidence: 85%
See 2 more Smart Citations
“…The morphological characteristics observed for the control animal are consistent with those observed by Hanna et al (2008Hanna et al ( , 2010, McConville et al (2010), and Toner et al (2011) for F. hepatica specimens not exposed to anthelmintic. Spermatogonia and primary spermatocytes were observed to occupy the entire region of the testis tubule, thereby ensuring the production of viable sperm and, consequently, F. hepatica eggs.…”
Section: Microscopic Alterationssupporting
confidence: 85%
“…Two F. hepatica specimens from each animal were selected from and placed between slides and were fixed in Bouin solution for 24 hours. After this period, the specimens were histologically processed following the methodology of Toner et al (2011) with modifications, in which the specimens remained for 15 minutes in ethanol at 70 °G.L. Next, each specimen was cross-sectioned in the region that corresponded to the location of the reproductive system, which encompasses the right and left halves and the median plane.…”
Section: Microscopic Alterationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The loss of motility and the degeneration of the gastrodermal cells (seen by 72 h pt) (Toner et al, 2010b) would prevent the fluke from feeding and this would exacerbate the general disruption of the fluke. Changes to the reproductive system took place earlier: for example, the testis was severely affected by 48 h pt (Toner et al, 2011b) and no eggs were present in the uterus at this time (Toner et al, 2011a). The latter was due to the disruption of the ovary, vitelline follicles and Mehlis' gland, which provide the components for egg formation in the ootype (Toner et al, 2011a).…”
Section: Action Of Tcbzmentioning
confidence: 96%
“…One group of drugs derived from natural sources that has received much attention in recent years is the artemisinins. Semi-and fully-synthetic derivatives of the artemisinins are the mainstay of malaria treatment programmes and have been used against schistosomes (e.g., Woodrow et al, 2005;Utzinger et al, 2007). Several studies have demonstrated their activity against adult and juvenile F. hepatica under in vitro conditions and in the rodent (rat) model (results reviewed by Fairweather, 2009).…”
Section: New Drugsmentioning
confidence: 97%